Warm waters undermine cryptic female choice - Kustra, Matthew; Alissa, Louise; Rogers, Michaela; Molinari, M.; Stiver, Kelly; Marsh‐Rollo, Susan; Hellmann, Jennifer; Alonzo, Suzanne (bioRxiv (Cold Spring Harbor Laboratory), 2025)
Abstract Reproduction is often more thermally sensitive than survival. Thus, understanding the thermal sensitivity of reproductive interactions is crucial given global warming. However, it is unknown how temperature influences female control over fertilization after mating ( i.e., cryptic female choice). We tested how temperatures relevant to current conditions and climate change projections influence cryptic female choice in a marine fish, Symphodus ocellatus . Under typical conditions, females bias fertilization dynamics to favor dominant males. We find that warmer temperatures decrease female influence on sperm velocity and reduce the expected paternity of dominant males. Our results demonstrate that temperatures relevant to climate change can shift the balance between mate choice and male-male competition. Thus, climate change may influence sexual selection, leading to evolutionary changes in reproductive traits.
Keywords: Geology; Oceanography; dept.psy

Conflict and cooperation in male–male partnerships alter paternal care behavior in the ocellated wrasse - Hellmann, Jennifer; Stiver, Kelly; Marsh‐Rollo, Susan; Alonzo, Suzanne (Behavioral Ecology, 2025)
Keywords: Biology; Fish; Fishery; Genetics; Paternal care; Symphodus ocellatus; Wrasse; Zoology; dept.psy; parental care; plasticity; reproduction; sexual selection; temperature

Breaking the truth bias: the impact of comparable truth baselines and reality interview on veracity judgments by laypeople and police officers - Bogaard, Glynis; Nieuwkamp, Veerle; Colwell, Kevin (Police Practice and Research, 2025)
This study examined whether embedding baselining within the Reality Interview (RI) protocol enhances intuitive veracity judgments. Baselining involves using a person's truthful verbal behavior as a reference point for evaluating the veracity of subsequent statements. We hypothesized that access to a comparable truth baseline (CTB) would improve veracity judgment accuracy. Eyewitnesses of a mock crime were interviewed with the RI and instructed to respond either honestly or deceptively. Laypeople (Experiment 1) and police officers (Experiment 2) evaluated these statements with or without a CTB. With a CTB, laypeople showed significantly higher accuracy in detecting deception and a reduced truth bias. However, police officers showed no improvement, maintaining chance-level performance regardless of statement veracity. These findings suggest that CTBs enhance lie detection in laypeople but not in trained professionals. Future research should explore tailored approaches to improving veracity judgments, perhaps incorporating specific guidelines on how to best use available cues.
Keywords: Baseline (sea); Comparable Truth Baseline; Deception; Interview; Lie detection; Point (geometry); Protocol (science); Reality Interview; Statement (logic); Trustworthiness; dept.psy; lie detection; verbal cues

Pharmacotherapies for stimulant use disorder and co-occurring attention deficit hyperactivity disorder: protocol for a systematic review and a meta-analysis - Oliva, Henrique; Pulido-Saavedra, Alejandra; Paredes-Naveda, Alisson; Forselius, Emerson; Potenza, Marc; Jegede, Oluwole; Angarita, Gustavo (Frontiers in Psychiatry, 2025)
Background Stimulant use disorder (StUD) and attention-deficit/hyperactivity disorder (ADHD) frequently co-occur. This comorbidity complicates treatment and worsens clinical outcomes. Despite the high prevalence, shared vulnerability and clinical relevance of this comorbidity, evidence on effective pharmacotherapies among individuals with this dual diagnosis remains limited. Materials and methods This systematic review protocol is reported in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Protocols (PRISMA-P) statement and will include randomized controlled trials involving adults with comorbid StUD (cocaine, amphetamines, or methamphetamines) and ADHD. The following databases will be searched: PubMed, Embase, Scopus, and Web of Science. Covidence will be used to support independent screening and data extraction. Two reviewers will independently screen studies (title/abstract and full text). One author will extract data, which will be independently verified by a second reviewer. Quality assessment of included articles will be assessed using the Cochrane Risk of Bias instrument, and certainty of the evidence for each outcome will be assessed using Grading of Recommendations, Assessment, Development and Evaluations (GRADE) methodology. Primary outcomes include duration of continuous abstinence, odds of stimulant-negative urine samples, ADHD symptom changes, and medication adverse events. Where feasible, meta-analyses will be conducted using random-effects models. Significance and dissemination This review will synthesize existing evidence on the efficacy of pharmacotherapies (stimulants and non-stimulants) for individuals with co-occurring StUD and ADHD. The results of this study will likely inform clinical practice by evaluating outcomes such as reduction in stimulant use and abstinence, and improvement in ADHD symptoms. Findings will be disseminated through peer-reviewed publication and presentations to reach both clinical and academic audiences. Systematic review registration PROSPERO, CRD420250655356.
Keywords: Alternative medicine; Atomoxetine; Attention deficit hyperactivity disorder; Clinical psychology; Internal medicine; Medicine; Meta-analysis; Methylphenidate; Protocol (science); Psychiatry; Psychology; Stimulant; attention deficit hyperactivity disorder; co-occurring disorder; cocaine; dept.psy; methamphetamine; stimulant use disorder

Masked-Speech Recognition and Self-Reported Functional Listening in Autistic Young Adults - Wasiuk, Peter; Cook, Barbara; Irwin, Julia (Journal of Speech Language and Hearing Research, 2025)
Keywords: Active listening; Audiology; Autism; Cognitive psychology; Communication; Developmental psychology; Medicine; Perception; Psychology; Speech perception; dept.cmd; dept.psy

Attitudes About Aging and Beliefs About When you Have Been or Will be Your Best Self - Kahlbaugh, Patricia; Biblekaj, Viktoria; Shortell, Malori (The International Journal of Aging and Human Development, 2025)
Keywords: Anxiety; Clinical psychology; Developmental psychology; Gerontology; Healthy aging; Internalization; Medicine; Psychiatry; Psychology; Successful aging; dept.psy; peer-reviewed